A Same-Sex Couple Copes With End-of-Life Issues: A Case Materials Guide - Colby Croft; Jonathan Pletcher; Valerie L. Fulmer; Robert C.T. Steele; Hollis Day; Carla L. Spagnoletti (Association of American Medical Colleges, 2013)
Abstract Medical students in the United States receive a median of only 5 hours of instruction on lesbian, gay, bisexual, and transgender-related health topics during medical school. The topics typically covered include medical conditions that disproportionately affect the sexual minority population, such as depression, anxiety, substance use, and certain sexually transmitted diseases. However, it is important to recognize that sexual minorities may face unique barriers to health care, including discrimination and lack of access to providers who are sensitive to and competent in addressing their needs. Furthermore, policies surrounding medico-legal challenges, such as advanced directives and visitation rights, vary by region and institution and may not adequately represent the needs of same-sex couples. This resource is a standardized patient case featuring a same-sex couple facing end-of-life issues, including medico-legal challenges unique to same-sex couples. The case was developed for the Advanced Medical Interviewing course for second-year medical students at the University of Pittsburgh School of Medicine. In this course, students take turns interviewing standardized patients in a group, with a faculty member facilitating feedback. For this case, three to four students each have a turn to interview the patient and his/her partner over a 45-minute period of time. The case could be adapted for use in clinical clerkships for third- and fourth-year medical students, as well as for residents, fellows, and even faculty in certain settings. Since the case contains material that requires the ability to recognize and deal with emotion and to address sensitive health topics, it is not for beginning medical students. One potential obstacle that was anticipated but did not occur was discomfort among standardized patients with various religious and political beliefs in portraying a patient in a same-sex partnership. While we recognize that being a sexual minority is not by itself a political behavior, issues surrounding sexual minorities have a tendency to elicit strong responses from various political and religious groups. One explanation for the lack of discomfort is that the educational objectives of the case encouraged self-reflection and awareness of legitimate, documented issues faced by patients but did not promote a political agenda. In addition, the case scenario was a realistic representation of one that may be encountered in the hospital, so potential discomfort was limited by the objective nature of the fact-based case materials.